Knowledge of Pregnant Women About Breast Care with Compliance with Breast Care in the Butar Health Center Area, Pagaran District, North Tapanuli Regency in 2020 - Urhuhe Dena Siburian; Paruhum Tiruon Ritonga (Institute of Computer Science (IOCS), 2020)
Health development is carried out based on humanity, empowerment and independence, fair and equitable, as well as prioritizing and benefiting with special attention to vulnerable populations, including mothers, infants, children, the elderly, and poor families (Ministry of Health, 2010). Based on data obtained from the Butar Health Center, Pagaran District, the number of pregnant women in the third trimester in 2014 was 60 people. In Sipultak dolok village 7 people, in Lumban ina-ina village 5 people, in parhorboan village 9 people, in Banua Luhu village 9 people, in Dolok saribu village 7 people and in other villages 17 people.The results of the Chi-square test showed a value of or 0.001 <0.05, there was a relationship between the knowledge of pregnant women in the third trimester about breast care and adherence to breast care.